Diagnosis Tiroiditis Hashimoto pada Seorang Wanita dengan Hipotiroidisme Subklinis dan Trombositopenia: Laporan Kasus - Cahyani, Devi Aulia; Masita, Annisa Nur (SCRIPTA SCORE Scientific Medical Journal, 2024)
Background: Hashimoto’s Thyroiditis (TH) is a variety of autoimmune thyroid disorders. It discovered incidentally, asymptomatic and generally normal thyroid profile, therefore it might adventurous to be diagnosed. Objectives: To describe establishing TH diagnosis in a woman with subclinical hypothyroidism and thrombocytopenia. Case Illustration: A woman, 46 years old, referred fatigue, joints pain and neck lump for about ± a year, physical examination was found diffuse goiter, USG examination was found TIRADS 2, laboratory examination was found thrombocytopenia, euthyroid, anti-TPO 203,8 IU/mL. Discussion: USG was concluded solid lesion visualized typical thyroiditis without FNAB required and anti-TPO results was appropriate with TH predictor>121,0 IU/ml. Numerous of studies showed TH which occurred with secondary immune thrombocytopenia. Conclusion: Subclinical hypothyroidism which presented diffuse goiter and higher normal TSH required USG and anti-TPO examination for established its diagnosis. Persistent thrombocytopenia might be suspected as autoimmune thyroid disorder especially whether presented goiter. Latar Belakang: Tiroiditis Hashimoto (TH) merupakan penyakit autoimun kelenjar tiroid. Penyakit ini ditemukan secara insidental, asimptomatik dan umumnya profil tiroid dalam batas normal sehingga mendiagnosisnya menjadi tantangan tersendiri. Tujuan: Menjelaskan penegakan diagnosis TH pada wanita dengan hipotiroidisme subklinis dan trombositopenia. Ilustrasi Kasus: Seorang wanita 46 tahun mengeluhkan cepat lelah, linu, benjolan leher selama ±1 tahun, pemeriksaan fisik didapatkan goiter difus, pemeriksaan USG didapatkan TIRADS 2, pemeriksaan laboratorium didapatkan trombositopenia, eutiroid, anti-TPO 203,8 IU/mL. Pembahasan: USG disimpulkan lesi solid mengesankan tiroiditis tanpa perlu FNAB dan anti-TPO sesuai dengan prediktor TH >121,0 IU/ml. Banyak studi menyebutkan TH yang disertai immune thrombocytopenia sekunder. Kesimpulan: Hipotiroidisme subklinis berupa goiter difus dan TSH sedikit meningkat perlu dilakukan USG dan anti-TPO untuk penegakan diagnosisnya. Trombositopenia persisten dapat dicurigai penyakit autoimun tiroid terutama bila terdapat goiter.